Uma fábrica-cidade: percepções de duas gerações de trabalhadores - Pires, Andréia Juliana (2020)
This dissertation aims to get to know the perceptions of young and adult workers of Companhia Brasileira de Alumínio about the company they work for. CBA developed peculiar relations with its workers and with the municipality of Alumínio in general, relations common to a specific type of factory: the city-factories. The concept of generation was central to this study. From Karl Mannheim's sociological approach, we sought to understand whether the perceptions that workers presented about the factory were impacted by the dimensions that characterize generational groups. For this, an exploratory and qualitative research was carried out through semi-structured interviews with six employees (five men and one woman), of different ages, aiming to understand similarities and differences between young and adult workers on the image formed by company, forms of entry, working conditions, career and the relationship between young people and adults, in addition to looking at their projects for a recent future amid profound changes in the world of work. The analysis of the interviews showed that the adults showed a stronger bond with the company, including an affective one, strongly influenced by the family context. Young people were more reticent in relation to the experience in the company, with more critical and problematic statements, revealing differences in perceptions in relation to adults. At the same time, it is also possible to conclude that the boundaries that delimit the perceptions of young people and adults have not always been shown to be rigid, being that sometimes they are attenuated and made more flexible, showing the complexity of the contradictions, recurrences and ambiguities that emerge in the workers' statements.